Criminal Liability of Hospitals and Medical Personnel for Medical Malpractice in Indonesia - Mulyana Riskiawati Pratiwi; Azizul Hakiki (Fakultas Hukum Universitas Bhayangkara Surabaya, 2026)
Medical malpractice cases represent a serious concern in healthcare services, as they have the potential to cause physical harm, psychological distress, and even death to patients. This study aims to analyze the forms of criminal liability imposed on hospitals and medical personnel in malpractice cases, based on a review of Court Verdict Number 85/Pdt/2021/PT PAL. The research adopts a normative juridical approach with a case study method, examined through applicable legislation, legal doctrine, and an analysis of the court decision's substance. The findings indicate that in the aforementioned decision, legal responsibility was not solely attributed to individual medical personnel, but extended to the hospital institution as a party bearing administrative and operational responsibility for healthcare services. The panel of judges determined that negligence had occurred in the application of standard medical procedures, alongside the hospital's failure to exercise adequate supervision over its medical staff. This decision serves as a significant precedent in strengthening the criminal dimension within the domain of medical malpractice, and affirms that hospitals cannot absolve themselves of legal responsibility when ethical and professional violations are committed by medical personnel under their institutional authority.